Validation of risk scores for permanent pacemaker implantation after TAVR. (14th October 2021) - Fugar, S; Deka, K; Anderson, C; Lama Von Buchwald, C; Geroux, R; Al-Amoodi, M; White, J; Kavinsky, C
Abstract: Background: Despite advances in transcatheter aortic valve replacement (TAVR) technology, High grade atrioventricular block (AVB) requiring permanent pacemaker (PPM) implantation remains a frequent complication after the procedure. National inpatient sample (NIS) score and the PACeR risk cores have been developed to help identify patients at an increased risk of requiring PPM. Purpose: We sort to validate both risk stratification tools developed to predict the need for PPM after TAVR. Methods: This is a single center retrospective study using consecutive patients who presented for TAVR at our institution from May 2012 till December 2020. Components from the two-scoring system previously published in literature was applied. Predictive accuracy of the scores were assessed using the C-statistics for discrimination and the Hosmer-Lemeshow goodness of fit test for calibration. Results: A total of 663 patients underwent TAVR over the study period. Of those, 101 were excluded. The final cohort included in the analysis were 562 patients. Fifty-seven patients (10.1%) required PPM. In both scoring, higher scores suggested increased risk of PPM implantation (Figure 1). PACeR and NIS scores showed an area under the curve of 0.750 and 0.699 respectively Figure 2. Model calibration showed a P-value of 0.799 over PACER and 0.583 for the NIS score (P>0.5 implying a good fit). Conclusion: The PACer risk score and NIS models were both validated in our database with acceptable outcomes. Overall, the PACeR risk scores proved to be more accurate in our database. Further studies in larger patient cohorts are needed to further validate these models. FUNDunding Acknowledgement: Type of funding sources: None.